2021
DOI: 10.3748/wjg.v27.i9.835
|View full text |Cite
|
Sign up to set email alerts
|

Progressive liver injury and increased mortality risk in COVID-19 patients: A retrospective cohort study in China

Abstract: BACKGROUND Liver injury is common and also can be fatal, particularly in severe or critical patients with coronavirus disease 2019 (COVID-19). AIM To conduct an in-depth investigation into the risk factors for liver injury and into the effective measures to prevent subsequent mortality risk. METHODS A retrospective cohort study was performed on 440 consecutive patients with relatively severe COVID-19 between January 28 and March 9, 2020 at To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…In addition, our findings indicated that an age > 60 years, diabetes mellitus and increased serum ferritin levels were independent strong predictors of mortality among patients with COVID-19 presenting liver injury. These observations are consistent with recent studies[ 10 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, our findings indicated that an age > 60 years, diabetes mellitus and increased serum ferritin levels were independent strong predictors of mortality among patients with COVID-19 presenting liver injury. These observations are consistent with recent studies[ 10 ].…”
Section: Discussionsupporting
confidence: 94%
“…All published literature which analyzed liver biochemical parameters in COVID-19 patients was examined through databases and shown in Table 1 [ 5 , 6 , 11 , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. Based on previous studies, liver biochemical parameters abnormalities were defined as the elevation of the following liver enzymes in serum: ALT > 40 U / L, AST > 40 U / L, and total bilirubin> 1.20 mg/d l. As in a previous study, we defined ALT and/or AST over three times upper limits of normal (ULN), and/or total bilirubin over two times ULN as liver injury [7] .…”
Section: Methodsmentioning
confidence: 99%
“…Severe ALI (>20 upper limit of normal transaminase levels) is uncommon occurring in <0.1% of infected patients 7. ALI reflected by increased transaminases and bilirubin was related to disease severity and poor outcome of COVID-19 8. Increases in gamma glutamyl transferase (γGT) and alkaline phosphatase (AP) are less frequently observed and found more in the later course of disease, whereas moderate increases in AST, ALT and bilirubin are a very common feature in COVID-19 disease 9.…”
Section: Covid-19: Liver Manifestations and Pathophysiological Aspectsmentioning
confidence: 99%